Iodine monoxide at a clean marine coastal site: observations of high frequency variations and inhomogeneous distributions - R. Commane; K. Seitz; C. S. E. Bale; W. J. Bloss; J. Buxmann; T. Ingham; U. Platt; D. Pöhler; D. E. Heard (Atmospheric Chemistry and Physics, 2011)
The first in situ point observations of iodine monoxide (IO) at a clean marine site were made using a laser-induced fluorescence instrument deployed at Mace Head, Ireland in August 2007. IO mixing ratios of up to 49.8 pptv (equivalent to pmol mol−1; 1 s average) were observed at day-time low tide, well in excess of previous observed spatially-averaged maxima. A strong anti-correlation of IO mixing ratios with tide height was evident and the high time resolution of the observations showed IO peaked in the hour after low tide. The temporal delay in peak IO compared to low tide has not been observed previously but coincides with the time of peak aerosol number previously observed at Mace Head. A long path-differential optical absorption spectroscopy instrument (with a 2 × 6.8 km folded path across Roundstone Bay) was also based at the site for 3 days during the point measurement observation period. Both instruments show similar temporal trends but the point measurements of IO are a factor of ~6–10 times greater than the spatially averaged IO mixing ratios, providing direct empirical evidence of the presence of inhomogeneities in the IO mixing ratio near the intertidal region.